Analysis of different current density conditions in the electrodialysis of zinc electroplating process solution. Issue 13 (2nd September 2017) - Bittencourt, Sérgio Deitos; Marder, Luciano; Benvenuti, Tatiane; Ferreira, Jane Zoppas; Bernardes, Andréa Moura
ABSTRACT: The use of currents below and above the limiting one for the treatment by electrodialysis of a solution prepared as a surrogate of a rinse water of the acid zinc electroplating processes was studied. The ionic transport behavior was evaluated by chronopotentiometry. The limiting current values were obtained through current–voltage curves. The trials performed with different current densities showed that the electrodialysis removed at least 98% of the contaminants without insoluble species precipitation on membrane surfaces. The water reuse is possible after electrodialysis treatment with current densities above the limiting one and considering a demineralization rate of 60%.